2017
DOI: 10.1155/2017/6180904
|View full text |Cite
|
Sign up to set email alerts
|

Higher Ratio of Abdominal Subcutaneous to Visceral Adipose Tissue Related with Preservation of Islet β-Cell Function in Healthy Individuals

Abstract: Objective To investigate the relationship between abdominal adipose tissue distribution, β-cell function, and insulin sensitivity (IS) in a Chinese population. Methods One hundred and eighty-eight healthy subjects (healthy group), 239 with normal glucose, and 1~4 abnormal metabolic traits (metabolic dysfunction group, MD group) and 125 with hyperglycemia (hyperglycemia group) were studied. HOMA-IR, HOMA-B, Matsuda index, early- (I0–30/G0–30) and late-phase (I30–120/G30–120) insulin responses and the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Unexpectedly, we found that the relative VAT volume; VATR was significantly lower indicating a relative increase in ASAT. VATR has previously been found to be superior to VAT volume as a measure of VAT risk (5961) and is typically measured by comparing the ratio of visceral to subcutaneous adipose tissue, either from the thigh (62) or as presented in this paper, the abdomen (VATR) (63). A clinical study by Porter et al compared the metabolic and cardiovascular disease risk between people with either high or low VAT in conjunction with high or low volumes of subcutaneous adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, we found that the relative VAT volume; VATR was significantly lower indicating a relative increase in ASAT. VATR has previously been found to be superior to VAT volume as a measure of VAT risk (5961) and is typically measured by comparing the ratio of visceral to subcutaneous adipose tissue, either from the thigh (62) or as presented in this paper, the abdomen (VATR) (63). A clinical study by Porter et al compared the metabolic and cardiovascular disease risk between people with either high or low VAT in conjunction with high or low volumes of subcutaneous adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…β cell function was assessed by homeostasis model assessment of β cell function (HOMA-β) [20]. Insulin resistance was estimated by index of homeostasis model assessment of insulin resistance (HOMA-IR) [20], quantitative insulin sensitivity check index (QUICKI) [21] and the Matsuda insulin sensitivity index (Matsuda ISI) [21] Measurement of body fat distribution Measurement of abdominal subcutaneous and visceral fat Participants were examined using abdominal coil magnetic resonance imaging (MRI; 3-Tesla whole-body scanner; SIEMENS 3.0 T MAGNETOM Verio; Siemens Healthcare Sector, Germany), as described previously [18,22]. The same radiologist performed all abdominal MRI scans.…”
Section: Anthropometric Measurements and Biochemical Evaluationsmentioning
confidence: 99%
“…In the nonpregnant state, a direct mechanistic link between adipose tissue function and systemic glucose homeostasis is supported by numerous lines of evidence. These include a strong epidemiological correlation between subcutaneous adipose tissue size and mitigation of metabolic and cardiometabolic risk (15)(16)(17)(18)(19)(20), extreme insulin resistance and hyperglycemia in congenital and acquired lipodystrophies (21)(22)(23), mitigation of insulin resistance in mice by genetic expansion of subcutaneous adipose tissue (24)(25)(26)(27), and direct effects of adipose tissue on glycemic control (28)(29)(30)(31). All these lines of evidence converge on the notion that an impaired capacity of adipose tissue to retain lipids leads to systemic lipotoxicity and development of insulin resistance.…”
Section: Introductionmentioning
confidence: 97%